Segitiga Kebijakan dan Analisis SWOT Mengenai Implementasi Kebijakan PSBB dalam Penanggulangan COVID-19 di DKI Jakarta - Wati, Risa Laras; Elisabet, Belinda Meliana; Goenawan, Goalbertus; Nurhanifah, Nurhanifah; Pratomo, Hadi (UI Scholars Hub, 2021)
Introduction. DKI Jakarta is the province with the highest COVID-19 cases in Indonesia, with 10.123 confirmed cases as of 23th June 2020, and it was the first province to determine the status of Large-Scale Social Restrictions (PSBB). Objective To review the implementation of large scale social restrictions policy to formulate a strategy for implementing future policies Methods. The implementation of the DKI Jakarta PSBB policy was analyzed using a SWOT (Strength, Weakness, Opportunity, Threat) analysis. SWOT analysis is a strategic planning tool that is widely used in community development, health and education programs. The study uses secondary data in the form of PSBB policies obtained through the official website of the DKI Jakarta Provincial Government as well as news related to the DKI Jakarta PSBB policies published in print and electronic media in the period between 25 th February 2020 to 5 th June 2020 Results. The existence of support from community leaders, applications to support work and study from home, as well as support from the Central Government, TNI and Polri as well as community leaders are an opportunity to be able to implement policies optimally Conclusion. The PSBB policy has been well implemented because it has managed all aspects of people’s lives and has succeeded in suppressing the spread of COVID-19 in the capital city.